Anxiety and depression in rheumatologic diseases: the relevance of diagnosis and management - R. Torta; F. Pennazio; V. Ieraci (PAGEPress Publications, 2014)
The high prevalence of emotional disorders (anxiety, chronic stress, mood depression) in patients with pain during rheumatologic diseases (particularly fibromyalgia) is closely related to the common pathogenic mechanisms concerning emotions and pain. Therefore a prompt identification of any psychic component of pain, also by means of specific tools, is a must, because it can require an adjustment of the therapeutic approach by combining both an analgesic treatment and antidepressants and/or psychotherapeutic strategies.